2022
DOI: 10.1371/journal.ppat.1010294
|View full text |Cite
|
Sign up to set email alerts
|

Cellular ESCRT components are recruited to regulate the endocytic trafficking and RNA replication compartment assembly during classical swine fever virus infection

Abstract: As the important molecular machinery for membrane protein sorting in eukaryotic cells, the endosomal sorting and transport complexes (ESCRT-0/I/II/III and VPS4) usually participate in various replication stages of enveloped viruses, such as endocytosis and budding. The main subunit of ESCRT-I, Tsg101, has been previously revealed to play a role in the entry and replication of classical swine fever virus (CSFV). However, the effect of the whole ESCRT machinery during CSFV infection has not yet been well defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…Using an siRNA screen, the authors identified several ESCRT components that contribute to CSFV infection at different stages of infectious cycle, including entry. Comparable to what has been observed for JEV, the ESCRT-III components CHMP2 and CHMP4 localized to CSFV VRCs [ 53 , 60 ]. Although ESCRT components such as HRS, TSG101, VPS28 (ESCRT-I), EAP20 (ESCRT-II), ALIX, CHMP7, and VPS4 also contribute to VRC formation through their interactions with the nonstructural proteins NS3, NS4B, NS5A, and NS5B [ 60 ], the molecular mechanism by which these nonstructural proteins interact with host ESCRT components remains to be elucidated.…”
Section: Overview Of the Host Endosomal Sorting Complex Required For ...mentioning
confidence: 84%
See 1 more Smart Citation
“…Using an siRNA screen, the authors identified several ESCRT components that contribute to CSFV infection at different stages of infectious cycle, including entry. Comparable to what has been observed for JEV, the ESCRT-III components CHMP2 and CHMP4 localized to CSFV VRCs [ 53 , 60 ]. Although ESCRT components such as HRS, TSG101, VPS28 (ESCRT-I), EAP20 (ESCRT-II), ALIX, CHMP7, and VPS4 also contribute to VRC formation through their interactions with the nonstructural proteins NS3, NS4B, NS5A, and NS5B [ 60 ], the molecular mechanism by which these nonstructural proteins interact with host ESCRT components remains to be elucidated.…”
Section: Overview Of the Host Endosomal Sorting Complex Required For ...mentioning
confidence: 84%
“…A more comprehensive depiction of the mechanism for ESCRT-dependent VRC formation was provided in a recent study of classical swine fever virus (CSFV) infection [ 60 ]. Using an siRNA screen, the authors identified several ESCRT components that contribute to CSFV infection at different stages of infectious cycle, including entry.…”
Section: Overview Of the Host Endosomal Sorting Complex Required For ...mentioning
confidence: 99%
“…Many studies have also reported on the formation of viral replication complexes (VRC) by ESCRT, such as classical swine fever virus (CSFV) [ 22 ] and brome mosaic virus (BMV) [ 23 ]. As alphacoronavirus rearrange the ER of host cells to form DMVs, a platforms for viral replication [ 12 ], we thus speculated that ALIX and TSG101 may be recruited to DMV to promote virus replication.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the Crimean-Congo hemorrhagic fever virus relies on ESCRT components to enter cells via MVB [ 28 ]. Meanwhile, TSG101, VPS25, CHMP4B, and CHMP7 play important roles in clathrin-mediated endocytosis of classical swine fever virus [ 22 , 29 ]. Hence, it follows that ESCRT is also involved in viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…ESCRT-III contains 12 α-helical charged multivesicular body proteins known as CHMP1A, CHMP1B, CHMP2A, CHMP2B, CHMP3, CHMP4A, CHMP4B, CHMP4C, CHMP5, CHMP6, CHMP7, and IST1, and it plays a key role in mediating cellular membrane constriction ( 17 , 18 ). The ESCRT machinery not only is required in cellular processes like plasma membrane repair but also is hijacked by some viruses in different stages of propagation, especially the budding stage ( 19 22 ). In these cases, viruses usually encode some conserved peptides, called the L-domain, as an adaptor to recruit ESCRT-associated proteins and utilize them to catalyze membrane fission events.…”
Section: Introductionmentioning
confidence: 99%